"The right to lead": Navajo language, dis‐citizenship, and Diné presidential politics. (3rd October 2019) - Jacobsen, Kristina; Thompson, Kerry F.
Abstract: This article examines the 2014 Navajo Nation presidential primary election and language debate as a window into the politics of Navajo heritage language and identity. Using Facebook posts written in response to a videotaped hearing testing the fluency of one of the candidates that subsequently went viral, we analyse social citizenship and stigmatized language identities through the lens of critical Diné (Navajo) language consciousness. Focusing on generational differences between speaker groups that undergirded this debate, we analyse (a) the fluency test itself and (b) online and ethnographic responses to the fluency test. Using discourse analysis of Facebook posts of both heritage language and new Navajo speakers, we show how new speakers in particular express investment in their language and Diné cultural continuity and, through their emphasis on the heterogeneity of contemporary Diné communicative practices, offer an alternative template for ways to move forward in Diné language reclamation efforts. Abstract : Questo articolo esamina le elezioni presidenziali Navajo del 2014 e il dibattito linguistico fioritovi attorno come una finestra sulla politica della lingua nativa e dell'identità Navajo. Usando alcuni post pubblicati su Facebook in risposta ad un filmato (divenuto virale) relativo ad un test realizzato per mettere alla prova la fluidità nel linguaggio nativo di uno dei candidati, analizziamo come l'appartenenza sociale e le identità linguistiche vengano stigmatizzate attraverso la lente critica della consapevolezza linguistica Diné (Navajo). Concentrandoci sulle differenze generazionali tra i gruppi di parlanti Diné che hanno partecipato a questo dibattito virtuale, analizziamo (a) il test di fluidità stesso e (b) i commenti al test, sia quelli rinvenuti online che quelli relativi alle risposte dateci sul campo durante una campagna etnografica. Usando l'analisi del discorso sui post scritti su Facebook da parlanti principianti della lingua Navajo e da altri studenti della lingua, mostriamo come i nuovi parlanti esprimono un forte attaccamento nella loro lingua e nella continuità culturale Navajo e, attraverso l'enfasi sull'eterogeneità delle pratiche comunicative contemporanee Diné, propongono modelli alternativi per nuovi processi di rappresentazione e recupero del linguaggio native. (Transl. Diego Pani)